2023
DOI: 10.1007/s40653-023-00540-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adverse Childhood Experiences on Mental Health and Suicidal Behaviors: A Study from Portuguese Language Countries

Abstract: Background: Research on adverse childhood experiences (ACEs) demonstrates that they can be associated with physical and mental health problems throughout the lifecourse. However, few studies have examined this topic in the Community of Portuguese Language Countries (CPLC). Objective: This study aims to assess the impact of ACEs on mental health and suicidal behaviors in a sample of participants from the CPLC. Participants and Setting: The sample consists of 1006 participants aged between 18 and 80 years (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(120 reference statements)
1
4
0
Order By: Relevance
“…The results show a high prevalence of ACEs ranging from 10.8% (physical neglect) to 59.7% (emotional abuse), with emotional abuse being the most reported category of ACEs. These results are like those found by other studies (Silva and Maia 2008;Silveira and Pereira 2023;Riedl et al 2020), which suggest that ACEs represent an alarming phenomenon with a significant impact in various cultural contexts. These findings can be associated with the relationship between ACEs and some risk factors that may influence parenting practices, including high parental stress related especially to lower-income situations (Crouch et al 2019), the lack of parenting skills such as little knowledge about child development (Stith et al 2009), and the repetition of dysfunctional family patterns, where parents who experienced ACEs in their childhood may be more likely to expose their children to the same experiences (Schickedanz et al 2021).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results show a high prevalence of ACEs ranging from 10.8% (physical neglect) to 59.7% (emotional abuse), with emotional abuse being the most reported category of ACEs. These results are like those found by other studies (Silva and Maia 2008;Silveira and Pereira 2023;Riedl et al 2020), which suggest that ACEs represent an alarming phenomenon with a significant impact in various cultural contexts. These findings can be associated with the relationship between ACEs and some risk factors that may influence parenting practices, including high parental stress related especially to lower-income situations (Crouch et al 2019), the lack of parenting skills such as little knowledge about child development (Stith et al 2009), and the repetition of dysfunctional family patterns, where parents who experienced ACEs in their childhood may be more likely to expose their children to the same experiences (Schickedanz et al 2021).…”
Section: Discussionsupporting
confidence: 91%
“…It is important to mention the need for greater investment in research in the future. Significant, positive correlations were found between the different categories of ACEs (e.g., positive strong correlations between physical and emotional abuse, as well as a positive strong correlation between domestic violence in the household and substance abuse in the household) (Silveira and Pereira 2023), suggesting that they are multidimensional and influence each other, not occurring in an isolated way (Karatekin 2017;Soares et al 2016;Riedl et al 2020), which is expected. Also, emotional abuse has a stronger correlation with depression (compared to anxiety), as evidenced in the recent literature (Elmore and Crouch 2020), showing that exposure to emotional abuse is positively associated with psychopathology in adults, especially with mood disorders (Martins et al 2014) A significant, positive, and strong correlation was found between depression and anxiety (Lou et al 2012).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations